Suspected glaucoma and early stage glaucoma: differential diagnostic criteria - R. V. Avdeev; A. S. Alexandrov; M. U. Arapiev; N. A. Bakunina; A. S. Basinskiy; D. A. Belaya; A. Y. Brezhnev; N. V. Volkova; L. M. Gabdrakhmanov; I. R. Gazizova; A. B. Galimova; V. V. Garkavenko; et al. (Российский офтальмологический журнал)
Purpose: to set out morphofunctional differences in the ophthalmic status between suspected glaucoma (SG) and the initial stage of primary open angle glaucoma (POAG), determine the values of interocular asymmetry of the analyzed parameters of fellow eyes and create a model able to distinguish, with high accuracy, between healthy subjects, SG patients and POAG patients relying on a few independent parameters. Material and methods. A multicenter study performed between July and November, 2016, by 34 research and clinical facilities of four countries (Russia, Belarus, Uzbekistan, and Moldova) involved 501 patients (824 eyes), of which 362 (72 %) were female and 139 (28 %) male. The main analyzed group consisted of 128 eyes with SG, 228 eyes with early stage POAG and 145 eyes of healthy subjects (the control group with comparable sex and age distribution and no history of glaucoma). The fellow-eye symmetry analysis group involved 190 eyes with SG, 336 eyes with early stage POAG and 220 eyes of 110 subjects with no glaucoma. Results. Differences were found in the structural and functional ophthalmologic parameters in early-stage POAG, SG, and the absence of glaucoma. The precision of SG and early POAG may be increased by cumulative consideration of several clinical parameters. Conclusions. The sensitivity and specificity of the integral index of condition prognostication increases when several parameters are analyzed simultaneously, as compared to the separate analysis of constituents. For citations: Avdeev R.V., Alexandrov A.S., Arapiev M.U., et al. Suspected glaucoma and early stage glaucoma: differential diagnostic criteria. Russian ophthalmological journal. 2017; 10 (4): 5-15. doi: 10.21516/2072-0076-2017-10-4-5-15 (In Russian).